Risks and benefits of rapid clozapine titration - Jeannie D. Lochhead; Michele A. Nelson; Alan L. Schneider (Mental Illness)
Clozapine is often considered the gold standard for the treatment of schizophrenia. Clinical guidelines suggest a gradual titration over 2 weeks to reduce the risks of adverse events such as seizures, hypotension, agranulocytosis, and myocarditis. The slow titration often delays time to therapeutic response. This raises the question of whether, in some patients, it may be safe to use a more rapid clozapine titration. The following case illustrates the potential risks associated with the use of multiple antipsychotics and rapid clozapine titration. We present the case of a young man with schizophrenia who developed life threatening neuroleptic malignant syndrome (NMS) during rapid clozapine titration and treatment with multiple antipsychotics. We were unable to find another case in the literature of NMS associated with rapid clozapine titration. This case is meant to urge clinicians to carefully evaluate the risks and benefits of rapid clozapine titration, and to encourage researchers to further evaluate the safety of rapid clozapine titration. Rapid clozapine titration has implications for decreasing health care costs associated with prolonged hospitalizations, and decreasing the emotional suffering associated with uncontrolled symptoms of psychosis. Clozapine is considered the most effective antipsychotic available thus efforts should focus on developing strategies that would allow for safest and most efficient use of clozapine to encourage its utilization for treatment resistance schizophrenia.